The Role and Importance of International Organizations in Maintaining Ecological and Human Security - Stajić, Ljubomir; Stanarević, Svetlana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
This paper presents key reflections on compromised ecological and human security. Man’s growing insecurity has been affected by global ecological issues in two ways, directly and indirectly. The former involves health implications of exposure to ultraviolet radiation, while the latter is linked to potential climate changes and malnutrition. Not all ecological hazards are global, but it is clear that they exacerbate local pollution-related concerns and that individual countries are not capable of addressing them on their own. How the perspective of human security can be incorporated into the analysis of environmental challenges and how the ecological dimension can be bolstered in the analysis of human security are some of the other issues examined in this paper. The paper aims to recognize the role and importance of international organizations based on conceptual, analytical and operational considerations of ecological and human security issues. Namely, through mutual cooperation and joint activities these organizations are making great efforts to produce results by analyzing the interaction between factors of global change and degradation of the environment and factors affecting human security. Among the more important organizations mentioned are the UN and several of its agencies and suborganizations that are part of the “UN family” (UNDP, UNESCO, UNU, UNU-EHS, UNEP, FAO) as well as a number of regional organizations such as OSCE and EU.